2016
DOI: 10.1093/brain/awv375
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury-induced immune deficiency syndrome enhances infection susceptibility dependent on lesion level

Abstract: Pneumonia is the leading cause of death after acute spinal cord injury and is associated with poor neurological outcome. In contrast to the current understanding, attributing enhanced infection susceptibility solely to the patient's environment and motor dysfunction, we investigate whether a secondary functional neurogenic immune deficiency (spinal cord injury-induced immune deficiency syndrome, SCI-IDS) may account for the enhanced infection susceptibility. We applied a clinically relevant model of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
140
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(154 citation statements)
references
References 51 publications
5
140
1
Order By: Relevance
“…*p Ͻ 0.05 versus WT control. Scale bars: C, 100 m; F, 50 m; inset, 5 m. tive effects of miR-155 deletion may also benefit SCI-induced neuropathic pain or autonomic dysfunction (Gris et al, 2004;Detloff et al, 2008;Schwab et al, 2014;Allison and Ditor, 2015;Tan et al, 2015;Brommer et al, 2016;Offiah et al, 2016). Further studies may also incorporate male mice because miR-155 may have different effects on cell metabolism and host physiology in males and females (Sipski et al, 2004;Furlan et al, 2005;Swartz et al, 2007;Luchetti et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*p Ͻ 0.05 versus WT control. Scale bars: C, 100 m; F, 50 m; inset, 5 m. tive effects of miR-155 deletion may also benefit SCI-induced neuropathic pain or autonomic dysfunction (Gris et al, 2004;Detloff et al, 2008;Schwab et al, 2014;Allison and Ditor, 2015;Tan et al, 2015;Brommer et al, 2016;Offiah et al, 2016). Further studies may also incorporate male mice because miR-155 may have different effects on cell metabolism and host physiology in males and females (Sipski et al, 2004;Furlan et al, 2005;Swartz et al, 2007;Luchetti et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
“…For example, inflammatory macrophages can cause axonal injury or inhibit axon regeneration after spinal cord injury (SCI) (Popovich et al, 1997;Kigerl et al, 2006;Kigerl et al, 2009;Prüss et al, 2011;Pool et al, 2012;Kroner et al, 2014). Therefore, therapies that boost intrinsic axon growth programs or that limit macrophage inflammatory signaling could improve spinal cord repair (Kobayashi et al, 1997;Popovich et al, 1999;Ramer et al, 2000;Sun et al, 2011;Bartus et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, subacute phases after SCI may be amenable to delayed protective interventions that target and control peripheral infections and other peripheral sources of circulating inflammatory stimuli. Epidemiological studies show that comorbid infections such as pneumonia worsen functional outcome after human SCI (128)(129)(130). Potential cellular mechanisms may involve prolonged inflammation at the lesion site that results in increased tissue damage.…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…3 In addition to increased morbidity and mortality, infections after SCI may affect neurologic recovery. 2,3 A recent study found that infections impaired the return of muscle strength up to 1 year postinjury; however, the long-term consequences remain uncertain.…”
mentioning
confidence: 99%
“…3 In addition to increased morbidity and mortality, infections after SCI may affect neurologic recovery. 2,3 A recent study found that infections impaired the return of muscle strength up to 1 year postinjury; however, the long-term consequences remain uncertain. 2 The aim of this study was to investigate whether infections occurring in an acute care setting after SCI affected long-term functional recovery and survival.…”
mentioning
confidence: 99%